Opportunity Stagnation in B2B Sales Process: An Operations Management Perspective from the Renewable Energy Sector - Kaasinen, Kalle (My University, 2026)
This study examines factors associated with lead stagnation in business-to-business (B2B) sales processes from an operations management perspective. In complex B2B environments, sales opportunities often remain inactive for extended periods, leading to inefficiencies in the sales pipeline. Drawing on concepts from operations management, particularly work-in-progress (WIP) and process flow, this study conceptualizes stagnation as the accumulation of partially processed sales opportunities within a structured process. The aim of the study is to increase understanding of why individual opportunities fail to progress and to identify the key factors associated with this phenomenon. The study focuses on a Nordic case company operating in the renewable energy sector. The theoretical background combines perspectives from B2B sales literature and operations management. Sales processes are conceptualized as stage-based flows in which opportuni-ties progress toward a final outcome, while operations management literature provides a framework for understanding waiting, accumulation, and process efficiency. In this context, stagnation is interpreted as a disruption in flow, potentially caused by imbalances between process input and capacity or by limitations in buyer readiness. The empirical analysis is based on transaction data collected from the case company’s cus-tomer relationship management (CRM) system. The dataset consists of 73 sales opportuni-ties in the Finnish market. The study applies a quantitative research design and uses binary logistic regression analysis to examine the relationship between buyer maturity, electricity consumption, and industry classification on the likelihood of an opportunity becoming stag-nant in the sales pipeline. The results show that buyer maturity is the most significant factor associated with opportuni-ty stagnation. A higher level of buyer maturity statistically significantly reduces the likelihood of stagnation. In contrast, electricity consumption and industry do not emerge as statistically significant explanatory factors in the multivariate analysis. These findings suggest that stag-nation in B2B sales processes is primarily related to the readiness of the buying organization rather than to structural characteristics of the market or the deal. From a theoretical perspective, the study contributes by integrating operations management concepts, particularly WIP and flow efficiency, into the analysis of sales processes. From a managerial perspective, the findings highlight the importance of assessing customer readi-ness, prioritizing qualified opportunities, and actively managing the sales pipeline to improve process efficiency and reduce accumulation.

Tässä tutkimuksessa tarkastellaan myyntimahdollisuuksien stagnointiin liittyviä tekijöitä yri-tysten välisissä (B2B) myyntiprosesseissa operaatiojohtamisen näkökulmasta. Monimutkai-sissa B2B-ympäristöissä myyntimahdollisuudet jäävät usein pitkäksi aikaa passiivisiksi, mikä heikentää myyntiputken tehokkuutta. Operaatiojohtamisen käsitteisiin, erityisesti kesken-eräiseen työhön (work-in-progress, WIP) ja prosessivirtaan, tukeutuen stagnointi käsitteellis-tetään osittain käsiteltyjen myyntimahdollisuuksien kertymiseksi prosessissa. Tutkimuksen tavoitteena on lisätä ymmärrystä siitä, miksi yksittäiset myyntimahdollisuudet eivät etene, sekä tunnistaa keskeiset tekijät, jotka ovat yhteydessä tähän ilmiöön. Tutkimus keskittyy poh-joismaiseen uusiutuvan energian toimialalla toimivaan tapausyritykseen. Tutkimuksen teoreettinen viitekehys yhdistää B2B-myynnin kirjallisuutta ja operaatiojohtami-sen näkökulmaa. Myyntiprosessit nähdään vaiheittaisina virtoina, joissa myyntimahdollisuu-det etenevät kohti lopputulosta, kun taas operaatiojohtamisen kirjallisuus tarjoaa viitekehyk-sen odottamisen, kertymisen ja prosessitehokkuuden ymmärtämiseen. Tässä kontekstissa stagnointi tulkitaan prosessivirran häiriöksi, joka voi johtua epätasapainosta prosessin syöt-teen ja kapasiteetin välillä tai ostajan valmiuteen liittyvistä rajoitteista. Empiirinen analyysi perustuu tapausyrityksen asiakkuudenhallintajärjestelmästä (CRM) ke-rättyyn transaktiodataan. Aineisto koostuu 73 myyntimahdollisuudesta Suomen markkinas-sa. Tutkimuksessa sovelletaan kvantitatiivista tutkimusasetelmaa ja analyysimenetelmänä käytetään binääristä logistista regressioanalyysiä, jolla tarkastellaan ostajan kypsyyden, säh-könkulutuksen ja toimialan yhteyttä myyntimahdollisuuden todennäköisyyteen stagnoitua myyntiputkessa. Tulokset osoittavat, että ostajan kypsyys on merkittävin myyntimahdollisuuksien stagnointiin liittyvä tekijä. Korkeampi ostajan kypsyystaso vähentää tilastollisesti merkitsevästi stagnoin-nin todennäköisyyttä. Sen sijaan sähkönkulutus ja toimiala eivät osoittautuneet tilastollisesti merkitseviksi selittäjiksi monimuuttuja-analyysissä. Tulokset viittaavat siihen, että stagnointi B2B-myyntiprosesseissa liittyy ensisijaisesti ostavan organisaation valmiuteen eikä markki-noiden tai kaupan rakenteellisiin ominaisuuksiin. Teoreettisesta näkökulmasta tutkimus kontribuoi yhdistämällä operaatiojohtamisen käsittei-tä, erityisesti WIP:n ja prosessivirran tehokkuuden, myyntiprosessien analyysiin. Liikkeenjoh-don näkökulmasta tulokset korostavat asiakasorganisaation valmiuden arvioinnin, myynti-mahdollisuuksien priorisoinnin sekä myyntiputken aktiivisen hallinnan merkitystä prosessite-hokkuuden parantamisessa ja kertymisen vähentämisessä.
Keywords: sale; processes; sales work; business-to-business marketing; business-to-business commerce; leadership (activity); process management; customer relationship management; purchases; customers; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master’s Programme in Industrial Engineering and Management; Industrial Management